2021
DOI: 10.1093/rheumatology/keab511
|View full text |Cite
|
Sign up to set email alerts
|

Brain white matter extracellular free-water increases are related to reduced neurocognitive function in systemic lupus erythematosus

Abstract: Objectives Brain white matter (WM) microstructural changes evaluated by diffusion MRI were well documented in patients with systemic lupus erythematosus (SLE). Yet, conventional diffusion tensor imaging technique fails to differentiate WM changes that originate from tissue alterations from those due to increased extracellular free water (FW) related to neuroinflammation, microvascular disruption, atrophy, or other extracellular processes. Here, we sought to delineate changes in WM tissue micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…A total of 18 articles that evaluated the effect of SLE on brain structure and their links with CD were included in this review (Figure 1) 12,1921,2336 . From these studies, eight utilized T1-weighted MRI 12,28,29,3133,35,36 , nine focused on diffusion MRI 1921,2427,30,34 , and one reported brain metrics from both modalities 23 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 18 articles that evaluated the effect of SLE on brain structure and their links with CD were included in this review (Figure 1) 12,1921,2336 . From these studies, eight utilized T1-weighted MRI 12,28,29,3133,35,36 , nine focused on diffusion MRI 1921,2427,30,34 , and one reported brain metrics from both modalities 23 .…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of studies are utilizing advanced MRI to investigate NPSLE 10 . Altered tissue microstructure has been reported in several brain regions of patients with and without NPSLE diagnosis when compared to healthy controls 11,1921 , and they have correlated with higher CD 20 . Overall, the presence of these associations even in the absence of clinical NPSLE diagnosis, suggest that brain involvement could be underdetected in SLE.…”
Section: Introductionmentioning
confidence: 99%
“…36 In patients with systemic lupus erythematodus, altered white matter structure correlated with cumulative glucocorticoids dosage and attentional deficits. 37…”
Section: Structural Mrimentioning
confidence: 99%
“…In children and adolescents with chronic glucocorticoids treatment, altered white matter microstructure has been observed in the uncinate fasciculus, a structure that regulates emotional processing through connecting the limbic system with prefrontal cortex 36 . In patients with systemic lupus erythematodus, altered white matter structure correlated with cumulative glucocorticoids dosage and attentional deficits 37 …”
Section: Exogenous Glucocorticoid Excessmentioning
confidence: 99%
“…These authors demonstrated a significant reduction in mean kurtosis at the posterior cingulate gyrus level, paired with decreased GM volume and reduction in NAA concentrations (SLE patients versus controls), suggesting a heavy impact on cognitive function of SLE patients, either with or without overt signs of NP involvement. Recently, the quantification of free extracellular water, measured exploiting a free-water (FW) imaging technique derived from DTI, confirmed an increase in the amount of extracellular free water in SLE patients with respect to healthy subjects [ 71 ]. Other researchers, instead, combined MTI with DTI, enrolling active NPSLE subjects, as well as non-NP SLE and controls [ 59 ].…”
Section: Advanced Dti Applications In Sle and Npsle: Multimodal Mri D...mentioning
confidence: 99%